EIB Working Paper 2022/03 Estimating conditional treatment effects of EIB lending to SMEs in Europe - European Investment Bank (European Investment Bank, 2022)
Small and medium-sized firms play a key role in the European economy. This paper uses statistical methods to estimate the effects of EIB financial support on European companies between 2008 and 2015. It shows that the effects of EIB supported lending on job creation and investments were larger for smaller and younger firms, and that longer maturities and more advantageous loan pricing are associated with larger employment and investment effects. The results suggest that benefits of the EIB support are more noticeable on an intensive margin, instead of on an extensive one.